Association between Psychosocial Factors and the Prevalence of Musculoskeletal Disorders among Internship Doctors in Malaysia - Firdaus Mohd Taib, Mohd; Hwan Yun, Myung; Md Tap, Masine (International Journal of Engineering and Technology, 2018)
Musculoskeletal disorders (MSDs) have been recognized as one of the main occupational health problems among health care workers. Many studies have suggested the influence of psychosocial factors on MSDs. The objective of this study is to look into the association between psychosocial factors and the prevalence of MSDs symptoms among internship doctors. 86 internship doctors completed a questionnaire which consists of demographic data, physical and psychosocial factors as well as musculoskeletal discomfort. Results show that 32.6% of them reported that they have musculoskeletal discomfort at a single body region during the last year, 16.3% reported two regions and 9.3% reported three regions where the most prevalent region affected was the neck area where 27.9% of the respondent reported they experienced symptoms or pain in this region, followed by wrists / hands (26.7%), lower back (19.8%) and upper back (14.0%). Meanwhile, there were association found between psychosocial factors and prevalence of MSDs in certain body regions. For instance, musculoskeletal symptom at neck, wrist/hands, upper and lower back regions have been found to be associated with five psychosocial stressors examined in this study. The results obtained indicate the influence of psychosocial factors on MSDs.